One Health in Practice: A Pilot Project for Integrated Care of Zoonotic Infections in Immunocompromised Children and Their Pets in Chile. (18th December 2015) - Peña, A.; Abarca, K.; Weitzel, T.; Gallegos, J.; Cerda, J.; García, P.; López, J.
Summary: Although pets provide physiological and psychological benefits to their owners, they are a potential source of zoonotic infections, especially for vulnerable individuals such as immunocompromised patients. During 1 year, we therefore performed a pilot project, which included 32 immunocompromised Chilean children and their family pets (35 dogs and 9 cats) with the aim of detecting, treating and preventing zoonotic infections. Children were examined by Infectious Diseases paediatricians and demographical and clinical information related to zoonotic infections were recorded. Pets were examined and sampled by veterinarians, who also administered missing routine vaccines and anti‐parasitics. During family visits, all members were informed and educated about zoonoses and a satisfaction survey was performed. Visits also included vector control and indoor residual spraying with pyrethroids. Children were re‐examined and re‐tested according to the findings of their pets, and all detected zoonotic infections were treated both in children and pets. Physical examination revealed abnormalities in 18 dogs (51.4%) and three cats (33.3%). Twenty‐eight (63.6%) of the pets were diagnosed with a zoonotic pathogen, and seven (15.9%) with a facultative pathogen. Most zoonotic agents were isolated from the pet's external ear and intestine. Bacteria with the highest pathogenic potential were Campylobacter jejuni and Brucella canis . In two children and their respective pets, the same zoonotic diseases were diagnosed (toxocariasis and giardiasis). Arthropods serving as potential vectors of zoonotic infections were found in 49% of dogs and 44% of cats. The pilot project was positively evaluated by the participating families. Our pilot project confirmed that pets are reservoir for various zoonotic agents in Chile and that the implementation of an integrated multidisciplinary programme was a valuable tool to prevent, diagnose and treat such zoonotic infections in vulnerable patients such as immunocompromised children.